Potensi Antibakteri Ekstrak Diethyl Ether Daun Mahkota Dewa (Phaleria macrocarpa (Scheff.) Boerl) terhadap Bakteri Pseudomonas aeruginosa dan Staphylococcus aureus (Journal of Tropical Pharmacy and Chemistry, 2025)
This study aims to test the antibacterial potential of diethyl ether extract of mahkota dewa leaves (Phaleria macrocarpa (Scheff.) Boerl) with the test method Minimum Inhibitory Concentration (MIC) and Minimum Kill Concentration (MBC) against the microbe, Pseudomonas aeruginosa and Staphylococcus aureus. The test materials were obtained by maceration of leaves with methanol, followed by partition using diethyl ether and n–butanol, each extract was tested its activity with solid dilution method. Solid dilution test results showed the active extract is extract of diethyl ether. Active extracts were further tested by using MIC and MBC. Value of MIC and MBC is determined by the most active and liquid dilution method followed by scratches on solid media. The results show that diethyl ether extract of mahkota dewa leaves (Phaleria macrocarpa [Scheff] Boerl.) Has the potential antibacterial against bacterium Staphylococcus aureus and Pseudomonas aeruginosa with MIC value of 0.025%, and the value of MBC, respectively - each is 0.4% for the bacterium Staphylococcus aureus, and 0.1% for the bacterium Pseudomonas aeruginosa.